Childhood in a rom/gypsy camp in southern-Italy:an anthropological perspective - Di Giovanni, Elisabetta (International Journal about Parents in Education, 2023)
The object of the study is the Rom/gypsy/ camp in Palermo, Sicily, in the south of Italy, where three groups of so-called “gypsies” or “travellers” live together; they originally came from the Balkans and have been settled in this zone for twenty years. Out of a population of about 300 individuals, as many as 55 children go to 7 different schools. The study is carried out using the anthropological method of participant observation. The aim of the research, which is still going on, is to monitor the progress of their schooling and to study their parents’ roles; particular attention is given to the fundamental interplay of relationships and socio-educational intervention in the capable hands of volunteers and the public administration. In fact, the latter have represented and continue to represent a solid support network during this process of encouraging the Rom/gypsy families to send their children to school. This support is needed right from the initial accompanying phase, and especially during the delicate support phase, from the moment the children pass from the Rom/gypsy world to the non-Rom/gypsy world of the “others”, the gagé.